Enforcement of European Competition Policy - Impact on Competition and Efficiency - Gordon J. Klein; Andrea Günster (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The study analyzes the impact of European antitrust enforcement on industry performance measured as competition intensity (Price Cost Margin) and productivity (labor productivity and distance to the frontier). For a panel of OECD countries on the industry level since 1988, we estimate the impact of an infringement decision by the European Commission on the competitive market structure. We find that enforcement has a considerable e ffect, both on competition intensity and on productivity. However, the impact di ffers with the anticompetitive economic conduct. Cartels behave as theoretically predicted with an increase in competition and productivity after the cartel break-up. The impact of vertical conduct is more complex, with positive and negative effi ciency eff ects of antitrust enforcement depending on the exclusivity of the vertical restraint.
Keywords: L40; K21; K20; 330